Pilus Adhesin RrgA Interacts with Complement Receptor 3, Thereby Affecting Macrophage Function and Systemic Pneumococcal Disease - Sofia Orrskog (American Society for Microbiology, 2013)
ABSTRACT Pneumococcal pili have been shown to influence pneumococcal colonization, disease development, and the inflammatory response in mice. The role of the pilus-associated RrgA adhesin in pneumococcal interactions with murine and human macrophages was investigated. Expression of pili with RrgA enhanced the uptake of pneumococci by murine and human macrophages that was abolished by antibodies to complement receptor 3 (CR3) and not seen in CR3-deficient macrophages. Recombinant RrgA, but not pilus subunit RrgC, promoted CR3-mediated phagocytosis of coated beads by murine and human macrophages. Flow cytometry showed that purified CR3 binds pneumococcal cells expressing RrgA, and purified RrgA was shown to interact with CR3 and its I domain. In vivo, RrgA facilitated spread of pneumococci from the upper airways and peritoneal cavity to the bloodstream. Earlier onset of septicemia and more rapidly progressing disease was observed in wild-type mice compared to CR3-deficient mice challenged intranasally or intraperitoneally with pneumococci. Motility assays and time-lapse video microscopy showed that pneumococcal stimulation of macrophage motility required RrgA and CR3. These findings, together with the observed RrgA-dependent increase of intracellular survivors up to 10 h following macrophage infection, suggest that RrgA-CR3-mediated phagocytosis promotes systemic pneumococcal spread from local sites. IMPORTANCE Streptococcus pneumoniae is a major contributor to morbidity and mortality in infectious diseases globally. Symptomatology is mainly due to pneumococcal interactions with host cells leading to an inflammatory response. However, we still need more knowledge on how pneumococci talk to immune cells and the importance of this interaction. Recently, a novel structure was identified on the pneumococcal surface, an adhesive pilus found in about 30% of clinical pneumococcal isolates. The pilus has been suggested to be important for successful spread of antibiotic-resistant pneumococcal clones globally. Here we sought to identify mechanisms for how the pneumococcal pilin subunit RrgA contributes to disease development by interacting with host immune cells. Our data suggest a new way for how pneumococci may cross talk with phagocytic cells and affect disease progression. An increased understanding of these processes may lead to better strategies for how to treat these common infections.